End-to-End Image Simulator for Optical Imaging Systems: Equations and Simulation Examples. (15th January 2013) - Coppo, Peter; Chiarantini, Leandro; Alparone, Luciano
Abstract : The theoretical description of a simplified end-to-end software tool for simulation of data produced by optical instruments, starting from either synthetic or airborne hyperspectral data, is described and some simulation examples of hyperspectral and panchromatic images for existing and future design instruments are also reported. High spatial/spectral resolution images with low intrinsic noise and the sensor/mission specifications are used as inputs for the simulations. The examples reported in this paper show the capabilities of the tool for simulating target detection scenarios, data quality assessment with respect to classification performance and class discrimination, impact of optical design on image quality, and 3D modelling of optical performances. The simulator is conceived as a tool (during phase 0/A) for the specification and early development of new Earth observation optical instruments, whose compliance to user's requirements is achieved through a process of cost/performance trade-off. The Selex Galileo simulator, as compared with other existing image simulators for phase C/D projects of space-borne instruments, implements all modules necessary for a complete panchromatic and hyper spectral image simulation, and it allows excellent flexibility and expandability for new integrated functions because of the adopted IDL-ENVI software environment.